Decision-making skills: An assessment among adolescents in surat city - Rutu Sanjaybhai Buch; Mohua Moitra; Rahul Damor; Naresh Chauhan (Wolters Kluwer Medknow Publications, 2021)
Introduction: This study assessed the process of decision-making among adolescents and the factors affecting it and also explored the styles of decision-making among adolescents. Methodology: A cross-sectional study using purposive sampling was carried out involving 1177 college-going students aged between 17 and 19 years. General Decision-Making Style (GDMS) and semi-structured questionnaire was used to collect data. Data were analyzed with the help of SPSS and AMOS. Exploratory and confirmatory factor analyses were run. Results: Good decision-making process was seen among 76.9% of the students. Kaiser-Meyer-Olkin verified that sampling adequacy was 0.8. Scree plot and Monte Carlo parallel analysis were suggestive of four factors which were logically intuitive, avoidant, dependent, and spontaneous styles of making decisions. Cronbach's alpha was 0.7 for GDMS. Staying arrangement, paternal education, fantasy scale score, perspective-taking score, personal distress score, problem-solving, self-esteem, creative thinking, and coping with stress were found statistically significant with decision-making process. While, on confirmatory factor analysis, a five-factor model was found to be fit with minimum discrepancy/degrees of freedom value of 2.68, root mean square error of approximation: 0.038, Comparative Fit Index (CFI): 0.927, Normed Fit Index (NFI): 0.890, parsimony CFI: 0.66, and parsimony NFI: 0.634. A high correlation was observed between rational and intuitive styles. Conclusion: The process of decision-making was found to be good, but styles of making decisions were overlapping